Fast track open aortic surgery: reduced post operative stay with a goal directed pathway. - Murphy, M; Richards, T; Atkinson, C; Perkins, J; Hands, L (2007)
OBJECTIVE: Open aortic aneurysm repair is traditionally associated with an extended hospital stay. The aim of this study was to examine the feasibility of reducing post-operative stay through the implementation of a fast-track, goal directed, clinical pathway for elective open aortic surgery. METHODS: A fast-track clinical pathway for aortic surgery was introduced in a regional vascular unit in September 2005. The pathway has daily goals and targets discharge for all patients on the 3rd post operative day. This study compares thirty consecutive discharges of unselected patients undergoing elective infra-renal aortic surgery following introduction of the pathway to the thirty consecutive cases preceding its introduction. Reasons for prolonged hospital stay were recorded. RESULTS: Six of thirty patients achieved discharge by Day 3. The median hospital stay reduced from 9 (range 4 to 17 days) to 5 days (range 2 to 12 days) following introduction of the pathway. There was one readmission within 30 days and no complications attributable to the pathway implementation. Cardiac complications and home planning were the most common causes of delayed discharge. CONCLUSION: Post-operative stay in patients undergoing standard elective open infra-renal aortic surgery can be safely reduced with the introduction of a goal directed pathway.